Applicability of Hilf`s Method to Compaction Control of Soil-Rock Mixtures - Brito, A. (2010)
The employment of non traditional materials, such as soil-rock mixtures, in the earthworks construction, by economical and environmental reasons, places some new challenges to compaction techniques and their control. Usually, this kind of material results from the rocky bulky extraction without explosives, and it can include some oversized particles (about 0.5 m or more). Recently, some attention was been addressed, due to the deficient behaviour presented by some roads, forcing, in many cases, the application of corrective measures. Frequently, these materials present an evolutive nature, with a friable coarser fraction, that, with the construction process and in the service phase, suffers an alteration of their nature and of their gradation. On the other hand, construction control of embankments constituted by soil-rock mixtures is still a subject that needs investigation, considering that it is necessary to extrapolate current test results, been reach by truncated gradation, for the real construction conditions. The behaviour of these materials depends of the relative percentage of theirs constituents, becoming close to a soil, if the fine fraction is large and the coarser material is scattered in it, or close to a rockfill if the coarser material is in contact to each other and the fines occupy the space between them. One of the control methods widely used in Portugal for in embankments is the Hilf’s method, since it does not need a previous knowledge of the materials characteristics. Nevertheless, this method was developed for fine soils. So, having in to account the materials from Odelouca Dam shells (weathered schist with a significant fraction of oversized particles), presently being constructed in South of Portugal, this article presents results from an investigation laboratory study relatively to the applications conditions and the applicability of Hilf’s method to coarse soils and soil-rock mixtures. A series of laboratory tests was performed and the obtained results were compared. Some conclusions are drawn about the applicability of this method.